PENERAPAN MEDIASI PENAL OLEH PENYIDIK TERHADAP TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DI KEPOLISIAN RESOR KOTA PEKANBARU - Adrizal, Ahmad; ', Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The punishment of perpetrators of domestic violence is set forth in Law Number 23 of 2004 regarding the abolition of domestic violence, but in reality not all applicable in the law is applied in the settlement of cases of domestic violence. Police investigators may also apply penal mediation taken by using the discretionary method approach. This is what is applied by the Pekanbaru City Police Investigator against several cases of domestic violence in Pekanbaru Ciy. The purpose of this thesis writing, namely to know the mediation penal arrangements by investigators against domestic violence in Pekanbaru Town Police, the implementation of penal mediation by investigators against domestic violence in Pekanbaru City Police, constraints and efforts in the process of mediating penal Conducted by investigators against domestic violence crime at Pekanbaru City Police Department. From the results of the study based on three problem formulas there are three main points that can be concluded, first the regulation of penal mediation on domestic violence cases is not yet in the rules governing domestic violence. The second application of penal mediation conducted by Pekanbaru City Police investigator using discretion method and with ADR in decision of Kapolri. The three obstacles in the mediation process penal done by the investigator to the crime of violence in the household is the basis of the rules that regulate the penal mediation and penal mediation itself is very contrary to the purpose and punishment principleKey Words: Mediation-Penal-Violence